Search for neutral MSSM Higgs bosons decaying to mu(+) mu(-) in pp collisions at root s=7 and 8 TeV - Khachatryan, V. (2016)
search for neutral Higgs bosons predicted in the minimal supersymmetric standard model (MSSM) for mu(+) mu(-) decay channels is presented. The analysis uses data collected by the CMS experiment at the LHC in proton-proton collisions at centre-of-mass energies of 7 and 8 TeV, corresponding to integrated luminosities of 5.1 and 19.3 fb(-1), respectively. The search is sensitive to Higgs bosons produced either through the gluon fusion process or in association with a b (b) over bar quark pair. No statistically significant excess is observed in the mu(+) mu(-) mass spectrum. Results are interpreted in the framework of several benchmark scenarios, and the data are used to set an upper limit on the MSSM parameter tan beta as a function of the mass of the pseudoscalar A boson in the range from 115 to 300 GeV. Model independent upper limits are given for the product of the cross section and branching fraction for gluon fusion and b quark associated production at root s = 8 TeV. They are the most stringent limits obtained to date in this channel. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.